Analisis Pengaruh Tingkat Pengangguran, Konsumsi Rumah Tangga, Dan Inflasi Terhadap Pertumbuhan Ekonomi Indonesia - Alhambra, Gita Fadillah; Iryani, Nelvia (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
One measure of the success of the development process is economic growth. The purpose of this study is to determine and analyze the long-term and short-term relationship of unemployment rates, household consumption, and inflation to Indonesia's economic growth. The method used in this study is the Error Correction Model (ECM) Test. The results of the study showed that the unemployment rate did not significantly affect Indonesia's economic growth as indicated by the probability value t (0.335) > α (0.05), household consumption significantly affected Indonesia's economic growth as indicated by the probability value t (0.000) < α (0.05), and inflation did not significantly affect Indonesia's economic growth as indicated by the probability value t (0.751) > α (0.05). The conclusion of this study is that the unemployment rate and inflation do not significantly affect Indonesia's economic growth, while household consumption significantly affects Indonesia's economic growth.